Influence of cardiac insufficiency as a complication of acute myocardial infarction on one-year mortality in patients treated with primary percutaneous coronary intervention - Trivunović, Božana M; Crvenkov, Teodora O; Matic, Dragan (Medicinski podmladak, 2020)
AbstractIntroduction: Cardiac insufficiency is the common and most severe complication of patients with acute ST segment elevation myocardial infarction (STEMI). For now, there is a little data on the incidence and prognosis of cardiac insufficiency in patients with STEMI in primary percutaneous coronary intervention (PCI) era.Aim: The aim of this investigation is to determine the incidence and impact of cardiac insufficiency on one-year mortality in patients with STEMI treated with primary PCI method.Material and methods: We analyzed data of consecutive patients with STEMI who were treated with primary PCI in the Coronary care unit of the Emergency Center in Belgrade due to acute STEMI Assessment of cardiac insufficiency was done according to the Killip classification. The primary outcome of the study was one year mortality.Results: Of the 700 consecutive patients with STEMI treated with primary PCI, cardiac insufficiency occurred in 160 patients (22.9%). One-year mortality in patients with heart failure was significantly higher than in patients who did not develop this complication (34.4% versus 5.4%; p